Growth hormone-releasing hormone antagonist MIA-602 inhibits inflammation induced by SARS-CoV-2 spike protein and bacterial lipopolysaccharide synergism in macrophages and human peripheral blood mononuclear cells - Granato, Giuseppina; Gesmundo, Iacopo; Pedrolli, Francesca; Kasarla, Ramesh; Begani, Laura; Banfi, Dana; Bruno, Stefania; Lopatina, Tatiana; Brizzi, Maria Felice; Cai, Renzhi; Sha, Wei; Ghigo, Ezio; et al. (Frontiers in Immunology, 2023)
COVID-19 is characterized by an excessive inflammatory response and macrophage hyperactivation, leading, in severe cases, to alveolar epithelial injury and acute respiratory distress syndrome. Recent studies have reported that SARS-CoV-2 spike (S) protein interacts with bacterial lipopolysaccharide (LPS) to boost inflammatory responses in vitro, in macrophages and peripheral blood mononuclear cells (PBMCs), and in vivo. The hypothalamic hormone growth hormone-releasing hormone (GHRH), in addition to promoting pituitary GH release, exerts many peripheral functions, acting as a growth factor in both malignant and non-malignant cells. GHRH antagonists, in turn, display potent antitumor effects and antinflammatory activities in different cell types, including lung and endothelial cells.However, to date, the antinflammatory role of GHRH antagonists in COVID-19 remains unexplored.Here, we examined the ability of GHRH antagonist MIA-602 to reduce inflammation in human THP-1-derived macrophages and PBMCs stimulated with S protein and LPS combination. Western blot and immunofluorescence analysis revealed the presence of GHRH receptor and its splice variant SV1 in both THP-1 cells and PBMCs. Exposure of THP-1 cells to S protein and LPS combination increased the mRNA levels and protein secretion of TNF-α and IL-1β, as well as IL-8 and MCP-1 gene expression, an effect hampered by MIA-602. Similarly, MIA-602 hindered TNF-α and IL-1β secretion in PBMCs and reduced MCP-1 mRNA levels. Mechanistically, MIA-602 blunted the S protein and LPS-induced activation of inflammatory pathways in THP-1 cells, such as NF-κB, STAT3, MAPK ERK1/2 and JNK. MIA-602 also attenuated oxidative stress in PBMCs, by decreasing ROS production, iNOS and COX-2 protein levels, and MMP9 activity. Finally, MIA-602 prevented the effect of S protein and LPS synergism on NF-кB nuclear translocation and activity. Overall, these findings demonstrate a novel antinflammatory role for GHRH antagonists of MIA class and suggest their potential development for the treatment of inflammatory diseases, such as COVID-19 and related comorbidities.